Treatment of anemia in inflammatory bowel disease--systematic review and meta-analysis. - Tomer Avni; Amir Bieber; Tali Steinmetz; Leonard Leibovici; Anat Gafter-Gvili (PLoS ONE)
Background Anemia is considered the most common systemic complication of inflammatory bowel disease (IBD). We aimed to provide all available evidence regarding the safety and efficacy of therapy existing today to correct anemia in IBD. Methods Systematic review and meta-analysis of randomized controlled trials that compared any treatment for anemia in patients with IBD. We searched electronic databases, conference proceedings and clinical trials registries. Two reviewers independently extracted data from included trials. The primary outcome was the effect of treatment for anemia in IBD on the hemoglobin (Hb) response, defined as rate of patients who achieved an increase of 2 g/dl in Hb concentration at the end of the follow-up. Secondary outcomes included disease severity scores, iron indices, Hb levels, inflammatory markers, adverse effects, and mortality. Dichotomous data were analysed by calculating the relative risk (RR) for each trial with the uncertainty in each result being expressed using 95% confidence intervals (CI). A fixed effect model was used, except in the event of significant heterogeneity between the trials (P<0.10, I(2)>40%), in which we used a random effects model. Results Nine trials fulfilled the inclusion criteria, to a total of 973 patients. We were able to perform meta-analysis for intravenous (IV) versus oral iron and for ESAs versus placebo. IV iron was associated with a higher rate of achieving Hb response in comparison to oral iron; RR 1.25 (95% CI 1.04-1.51, I(2) = 2%, 4 trials), CRP levels and disease activity indexes were not significantly affected by IV iron. IV iron was associated with a decrease in adverse events that required discontinuation of intervention and without an increase in serious adverse. Discussion Treatment for anemia in IBD should include IV iron and not oral iron replacement, due to improved Hb response, no added toxicity and no negative effect on disease activity.